Comparing Short Versus Long Persistency of Anthelmintics: Impacts on Dairy Sheep Production - Konstantinos V. Arsenopoulos; Eleni Michalopoulou; Elias Papadopoulos (Animals)
Introduction: Grazing dairy ewes are often heavily challenged by parasitic infections, which represent one of the most important concerns in sheep farming due to their impacts on dairy sheep production. Objectives: The objectives of the present study were (i) to compare the short (i.e., albendazole) and long (i.e., eprinomectin) persistent effect of these anthelmintics in reducing infections by gastrointestinal nematodes (GIN) in ewes and (ii) to determine these effects on milk yield and quality in naturally infected with GIN dairy ewes. Methods: On each farm, 40 selected ewes were divided into four similar groups on Day 0 based on their fecal egg counts (eggs per gram of feces; epg) as follows: Group 1—control group; Group 2—albendazole-treated group; Group 3—pour-on eprinomectin-treated group; Group 4—injectable eprinomectin-treated group. Fecal egg counts and coprocultures were performed on Days 0, 15, 30, 45, 60 and 75. The milk yield and milk quality (i.e., fat and protein concentration and somatic cell counts) were estimated on the aforementioned occasions. Results: Eprinomectin outperformed albendazole in treating gastrointestinal nematode infections in dairy ewes. Both pour-on and injectable eprinomectin formulations provided long-lasting protection by reducing fecal egg counts (i.e., from 92.1% to 99.9%). Furthermore, eprinomectin-treated ewes exhibited increased daily milk yield and improved milk composition in terms of fat and protein concentrations and somatic cell counts. Conclusions: These findings highlight the benefits of long-persistent efficacy of eprinomectin as a preferred anthelmintic treatment for lactating dairy ewes, offering enhanced productivity and milk quality, while addressing parasite resistance concerns.